NILAI TAMBAH KOPI ARABIKA PEGUNUNGAN DIENG - Azizi, Ernes Septina (Universitas Galuh, 2023)
Coffee is one of leading export commodities in Indonesia. Banjarnegara is one of the regencies in Central Java that has been increase coffee production, particularly the type of coffee grown in the Dieng Mountains. Farmers in the Dieng Mountains have not been able to process the coffee properly, resulting in them selling it in the form of cherry coffee. As a result, the significant profits are gained by coffee processors or shops. This research was conducted with the aim of analyzing the added value of Arabica coffee in the Dieng Mountains, which includes Ratamba, Babadan, Senggani, and Kalibening coffee. The research was conducted using the Hayami method. The results showed that the average profit level for the four types of coffee was 95%, or Rp 17,493/kg output. The average margin obtained was Rp 22,967, which can be considered quite significant. 3% margin percentage was obtained by labor income, 25% by other input contributions, and 72% by processors. The average price of powdered coffee was Rp 310,000/kg, and the average raw material price was Rp 6,000/kg. Currently, coffee supply chain actor are concerned about the increase in raw material prices, which is expected to cause consumer prices to rise and decrease demand.